Inclusion of paper packaging in a small fraction of the diet of confined lambs - da Silva, Mônica Márcia; de Almeida, Daniela Lázara; de Carvalho, Amanda; Maióli, Bruna Moreira; Klein, Vicenti Braun; Gonçalves, Leticia Aline; Carlis, Matheus Sousa de Paula; Gallo, Sarita Bonagurio (Frontiers in Animal Science, 2025)
IntroductionIn ruminant production systems, packaging is commonly used for the transport and storage of feed ingredients such as grains and minerals. The development of edible, cellulose-based packaging that can be safely ingested by ruminants offers a promising approach to reducing environmental waste on farms. This study aimed to evaluate the inclusion of edible paper packaging in the diets of lambs and its effects on nutrient digestibility, nitrogen balance, growth performance, carcass characteristics, and meat quality.MethodsTwenty crossbred lambs, 3 months old; initial body weight of 23.40 ± 1.00 kg, were randomly assigned to two dietary treatments: a control diet without packaging (CTL) and a diet including edible paper packaging (PACK). The experiment was in a completely randomized design, with two treatments and ten replications. Data were analyzed using Tukey’s test at a 5% significance level.ResultsNo significant differences (P > 0.05) were observed between treatments for dry matter intake or apparent nutrient digestibility. Growth performance was not affected (P > 0.05). However, cold carcass yield was reduced (P = 0.043), and higher cooking losses (P = 0.011) were observed in the PACK group.DiscussionThe inclusion of edible paper packaging can be used in lamb diets, as it did not alter dry matter intake or nutrient intake, and therefore did not affect production performance, most carcass characteristics, or meat quality, except for cold carcass yield and water loss during cooking.